EDUKASI BAHAYA APLIKASI PINJAMAN ONLINE ILEGAL - Krey, Thresia Hilda Mathelda Yenkase; Senandi, Winna Amelia Alfrida (JURNAL PENGABDIAN PAPUA, 2024)
This outreach activity with the title "Education on the Dangers of Illegal Online Loan Applications" was carried out as a form of applying science and technology within the PGRI Jayapura High School and the BKKBN Jayapura Youth Information and Counseling Center Association with the target of counseling participants being school children and teenagers. The aim of this activity is to provide an understanding of the dangers of using illegal online loan applications, the actions that need to be taken so that we avoid using illegal online loan applications, and regarding the legal rules regarding the use of illegal online loan applications. During the activity, the enthusiasm of the participants was visible, especially when providing responses during the question and answer session at the end of the activity. It is hoped that this activity will provide benefits to prevent the use of illegal online loan applications circulating in the community by irresponsible actors. Apart from that, it is hoped that this activity can also be an effort that is indirectly useful for protecting the people in Jayapura City. Keywords: illegal fintech, online loans, internet, illegal.